PENGARUH MODEL PEMBELAJARAN RADEC (READ – ANSWER – DISCUSS – EXPLAIN - CREATE) TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA - Tara Fatikhah Rakhma; Neneng Sri Wulan; Primanita Sholihah Rosmana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the results of PISA 2022 which show that students'reading ability in Indonesia is still low. Therefore, to overcome the low readingliteracy of students, the right learning model with a syntax that is easy toremember is needed, one of which is the RADEC (Read-Answer-Discuss-Explain-Create) learning model. This study aims to determine the influence of theapplication of the RADEC learning model on students' reading ability. This studyused a quasi-experimental design with one experimental class using the RADEClearning model and one control class using the Cooperative Script learning model.The research sample was 70 students from a total population of 113 students. Theresults of the study showed that there was a positive and significant relationshipbetween the RADEC learning model and the reading comprehension ability ofstudents in the experimental class.